Fannish boy: Examining blues fandom through British music periodicals. (1st March 2021) - Munshower, Alan; Johnson, Greg
Before online forums and social media groups allowed spaces for blues fans to share their love of the music, newsletters and periodicals created by blues societies and fans provided outlets for blues aficionados to connect with other fans, discographers, musicians and scholars through performance and album reviews, pilgrimage storytelling, descriptions of recent discoveries of rare sound recordings and much more. The University of Mississippi Blues Archive holds a large collection of blues periodicals, covering over 1000 unique titles, from over 25 countries, with a bulk date of 1963 to the present. Historically of interest to researchers of blues performance history, the collection also contains a wealth of insight to blues fandom and communities of music appreciation worldwide. This article explores pathways for examining blues fandom studies through the newsletter collection and highlights unique issues and perspectives found in the collection.